Infantile Systemic Hyalinosis (ISH): A Comprehensive Review of Its Genetic Basis, Clinical Spectrum, and Therapeutic Challenges - Maha Mashrq AlBayati; Wurood Kadhim Abed; Thualfakar Hayder Hasan (Journal of Biomedicine and Biochemistry, 2025)
Background: Infantile Systemic Hyalinosis (ISH) is a very rare and severe autosomal recessive disease, in which amorphous hyalineaceous material is deposited extensively in different tissues and presents a multisystemic clinical manifestation. This debilitating disease, based on a biallelic mutation of the ANTXR2 gene, is typically characterized by a course of infancy and progressive joint contractures, painful papules and macules on the skin, gingival hypertrophy, gastrointestinal dysfunction, and failure to thrive. Despite such melodies’ effects on people who are affected and it is a poorly-known disease that has few known therapeutic options. This systematic literature review seeks to summarize the knowledge on ISH, including acrylic-based knowledge, genetic foundation, molecular pathophysiology, etc., various clinical expressions, diagnostic and treatment implementations. The study will be going to explore the specific characteristics that separate ISH and its allele Juvenile Hyaline Fibromatosis (JHF), which is a counterpart and speaks of the problems in diagnosis and early intervention, which is vital, through pooling together information based on the case reports and literature reviews in the short term.ISH is a strong reminder of how complicated rare things can be genetic disorders. Increased sensitization among health professionals, as well as Speedy and precise diagnosis, plays the utmost role in maximizing supportive care, enhancing the lives of the affected infants.